Experimental analysis of bone marrow adipose tissue and bone marrow adipocytes: An update from the bone marrow adiposity society (BMAS) - Tencerova, M; Palmisano, B; Lucas, S; Attané, C; Ivaska; KK; Loisay; L; Ikushima, YM; Trivanovic, D; Corsi, A; Roque, A; et al. (Netherlands, 2025)
Bone marrow adipose tissue (BMAT) is physiologically linked to bone and energy metabolism, endocrine regulation, hematopoiesis and cancer-related processes. A key challenge in the field is that methods for isolating BMAT or bone marrow adipocytes (BMAds) are variable because there are no widely adopted standardized protocols. To generate awareness of this challenge and to establish uniformity in experimental approaches requiring isolation, storage and characterization of BMAT and BMAds, the Biobanking Working Group of the international Bone Marrow Adiposity Society (BMAS) has previously recommended experimental standards. This paper provides an update on this effort and presents current state-of-the-art methods and technical considerations for isolation and characterization of BMAT and BMAds, including currently available high-throughput omics approaches. This review provides a reference point based on the consensus view of BMAS investigators to support studies on biomedical, biological, biochemical and biophysical questions associated with bone marrow adiposity.